SPATIAL ANALYSIS OF RADON GAS CONCENTRATION DISTRBUTED AT BAGHDAD CITY USING REMOTE SENSING AND GEOGRAPHIC INFORMATION SYSTEM TECHNIQUESD - K. M. Al- Ramahi, F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Spatial analysis (spatial statistics) contain systematic techniques, that study actually geographic data have geographic properties such as topological and geometric, spatial analysis involve difference types of technique. Spatial analysis represented new understanding complex topics in form easy by any method or statistical for study area include mathematics and logic. Using function of point density which represented the Radon gas measurement geographic location, and limitation the density area by finding the radii (bandwidth) Kernel Density Estimation (KDE) techniques variation to reach interest regions and hotspot of point’s neighborhood. The aim of the research, applied the spatial statistical method to acknowledge concentrations of radon gas pollution for environmental and human life conservation, and focuses on the region affected by determination and orientation it in this method or tools for control outbreak to be facilitated, this potential possibility aid to avoid research randomly for radon gas pollution regions, this processing consist by extraction the spatial characteristics distribution that depending on distance measurements, by using geographic information system (GIS) technical, and which exploited Global Positioning system to accurate simultaneously the spectral bands of landsate satellite imagery to referencing the study area, and they have been determining the topology objects such as land cover (water, vegetation and soil) and land use, to connected with points measurement of Radon gas in Baghdad city only soils election, thought the soils were caused pollution based for objects type such as water and air, because, the natural formative of layer soils by decay of radioactive isotope Uranium with erosion the rocks and drift process with dissolved water or flood throughout the ages. Doing field the soil samples measurement by RAD7 Mobil detector for 58 point samples election, which represented using soil type such as vegetation land and land use touched with human life.